Integration of host gene regulation and oral microbiome reveals the influences of smoking during the development of oral squamous cell carcinoma - Liang, Dan; Ma, Xuemeng; Zhong, Xiaoyi; Zhou, Yinghua (Frontiers in Oncology, 2024)
ObjectiveThis study aims to investigate the regulation of host gene transcription and microbial changes during the development of oral squamous cell carcinoma (OSCC) associated with smoking.MethodsThe OSCC mouse model and smoking mouse model were established using 200 μg/mL 4-nitroquinoline-1-oxide (4NQO) in drinking water and exposure to cigarette smoke (four cigarettes per session, once a day, 5 days a week). Tongue tissues were harvested at 4 weeks and 16 weeks. Histopathological changes were evaluated using hematoxylin and eosin staining and Ki67 staining. RNA sequencing was performed on the mouse tongue tissues to identify differentially expressed genes (DEGs), and the results were validated by RT-PCR and immunohistochemistry. 16S rDNA sequencing was used to analyze changes in the oral microbiota during the early development of OSCC, identifying differentially abundant taxa associated with smoking. Finally, associations between the relative abundances of the oral microbiome and host gene expression were modeled using the Origin software.ResultsDEGs associated with smoking during the development of OSCC were identified. There were 12 upregulated genes, including NR4A3 and PPP1R3C, and 23 downregulated genes, including CD74 and ANKRD1. These genes were enriched in functions related to the signal transduction of cellular processes such as inflammation, differentiation, immunity, and PI3K/AKT, NF-κB signaling pathways. 4NQO and smoking treatment decreased oral microbial diversity and reduced the abundance of Bacteroidetes, Proteobacteria, and Lactobacillus but increased the abundance of Staphylococcus. Integrative analysis showed that the expression of CD74 was positively correlated with the relative abundance of Lactobacillus, while PPP1R3C was negatively correlated with Bacteroidota.ConclusionIn addition to characterizing host gene expression and the oral microbiome, our study explored the potential role of host–microbiome interactions in the development of OSCC. These findings enhance our understanding of smoking-related OSCC occurrence and development, providing new insights for its prevention.